Analysis of Deaf Students' Obstacles in Indonesian Writing Skills at SMPLB Dharma Asih Depok - Dara Minanda; Mohammad Umar Muslim (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2023)
This research discusses the factors that hinder deaf children at SMPLB Dharma Asih in writing using Indonesian. The purpose of this research is to provide an overview to stakeholders in providing the right method so that deaf children's writing skills can improve optimally. The method used in this research is descriptive qualitative. From the results of observations and data collection on the writing of deaf students of SMPLB Dharma Asih grades 1, 2, and 3 with a total representation of 5 students, there are many writing errors that are not in accordance with Indonesian language rules. After further analysis is also complemented by the interview process, this is caused by internal factors and external factors. Internal factors that hinder deaf students in writing include the low literacy skills of students and the tendency of students to mix sign language used for daily communication with Indonesian writing rules. While external factors that hinder deaf students' skills in writing include the school curriculum, the capacity of teachers, and the family background of deaf students who tend to be hearing people.